THE EFECTIVENESS OF UTILIZATION OF THE SCIENCE LABORATORY IN INTEGRATED SCIENCE LEARNING AT MTS UNGGULAN AL QODIRI 1 JEMBER - Winda Kuncorowati; Mohammad Wildan Habibi; Choiriya Tri Mosrifa; Mela Mahardika Ilafi (Science Education, Institut Agama Islam Negeri Ponorogo, 2021)
The purpose of this study was to determine the effectiveness of usingscience laboratories and the factors that affected the effectiveness of using science laboratories in supporting learning at Mts Unggulan Al-Qodiri 1 Jember. This research was a qualitative research. Data collection techniques in this study used observation guidelines and interview guidelines. The data obtained were from the results of interviews with one of the science teachers as well as the head of the laboratory at MTs Unggulan 1 Alqodiri Jember. The results showed that the use of the science laboratory at MTs Unggulan Al-Qodiri 1 Jember can be said to be effective in supporting learning in schools. This can be seen from the effectiveness of the use of science laboratories facilitated with complete equipment, it can be said to be 90%. The tools contained in MTs Unggulan Al-Qodiri 1 Jember are very effective in utilizing the Science Laboratory in Integrated Science Learning. Based on this explanation, the function of the laboratory as a means of strengthening students' understanding, increasing learning motivation and learning outcomes through science experiment at MTs Unggulan Al-Qodiri 1 Jember has beeneffective.